Anti-Inflammatory Effect Of Carica Papaya Leaves Extract In Male Wistar Rats Based On Variation Of Concentration - Vonna Aulianshah; Yelda Ratu Thaharah; Noni Zakiah; Rini Handayani (CV. Inara, 2024)
Treatment of inflammation is currently dominated by using synthetic drugs, which if used in cases of chronic inflammation such as hyperuricemia and rheumatoid arthritis will carry the risk of increasing side effects for the user. Papaya leaves as a potential herb in some communities are also used as a treatment for inflammatory conditions. The aim of this research was to determine the anti-inflammatory effect of papaya leaf extract in vivo based on variations in concentration in Wistar white rats. This research is an in vivo study using 25 male Wistar Rats and divided into 5 groups. Group I was given as a negative control (P0), the group used Diclofenac Sodium as a positive control (P1), the Carica papaya leaf extract test group with varying concentrations of 40% (P2), 50% (P3), and 60% concentration (P4). Carrageenan 1% is used as an inflammation inducer. The inflammation observation parameter in this study was the volume of edema in the rats' feet at 30 minute intervals for 180 minutes. The average percentage reduction in edema during 180 minutes of observation in the P2, P3 and P4 extract test groups was 81.00%, 78.33% and 81.00%, respectively. The positive control group (P1) showed a reduction of 81.66%, while the negative control was only 26%. The results of statistical tests show that there is an effect of giving the extract on reducing edema in mice compared to the negative control group. From these results it can be concluded that the ethanol extract of Carica papaya leaves with concentrations of 40%, 50% and 60% showed an anti-inflammatory effect on male Wistar rats.